Performance Analysis of Oil Palm Companies Based on Barcode System through Fit Viability Approach: Long Work as A Moderator Variable - Zulham; Lubis, Zulkarnain; Zarlis, Muhammad; Aulia, Muhammad Reza (Pandawan, 2023)
Novelty technology will be capable of increasing the performance company's coconut palm oil, one of them being the barcode system. So from that, I needed something to study to know how to influence suitability, continuity and use of the barcode system against the performance company coconut palm. Study this using a long working variable as a moderator variable. The study aims to analyze the effect of fit, viability, and use on the performance of a business company's coconut palm based on the Barcode System. Study this using 237 samples of employee data collected through stratified proportional random sampling at PT LNK from April 2022 to June 2022. Data were analyzed by SEM-PLS analysis with SMARTPLS software 3. An overview of the Barcode System via the Fit-Viability approach has been presented in the paper. Research results show that the performance of the business is affected by viability and use, but not affected by compatibility. Working time takes effect compatibility and compatibility to the assignment will be the taller when working long hours. Paper contributes to the development barcode system at PT LNK. Expected barcode system used by all companies coconut palm oil and can be integrated into the cloud-based data so that it could generate production data in real-time.